Exploring how IP marketing (media marketing) influences consumer shopping psychology through quantitative and empirical analysis - Zhang, Hang; Luo, Xiaohuan (Frontiers in Psychology, 2024)
As the concepts of intellectual property and media marketing have gained popularity, media marketing has gradually become an integral part of intellectual property marketing, and its use has become more widespread. However, the field of intellectual property marketing (media marketing) has become confused and faces challenges such as loss of uniqueness and weak consumer connections. Existing research efforts have focused on marketing strategies for branded intellectual property, but have neglected the important perspective of consumer psychology and behaviour. In this study, we use the AISAS model to segment digital marketing and delve into consumer psychology and behavioural factors that influence intellectual property marketing (media marketing). This exploration covers intellectual property content at the attention stage, intellectual property value at the interest stage, emotional trust at the search stage, mental consumption at the purchase stage and fan interaction at the sharing stage. We conducted a comprehensive analysis of the data using SPSS and AMOS, and integrated a consumer attitude questionnaire. The final findings confirm that intellectual property content, value, emotional trust, spiritual consumption and fan interaction all positively influence consumer psychology and behaviour. In addition, we make consumer-centric recommendations to extend the life cycle of intellectual property and promote sustainable brand development.